2012
DOI: 10.1098/rspa.2012.0247
|View full text |Cite
|
Sign up to set email alerts
|

Do dolphins benefit from nonlinear mathematics when processing their sonar returns?

Abstract: Dolphins have been observed to blow bubble nets when hunting prey. Such bubble nets would confound the best man-made sonar because the strong scattering by the bubbles generates 'clutter' in the sonar image, which cannot be distinguished from the true target. The engineering specification of dolphin sonar is not superior to the best man-made sonar. A logical deduction from this is that, in blowing bubble nets, either dolphins are 'blinding' their echolocation sense when hunting or they have a facility absent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…We developed a practical sonar system using this BiaPSS (Biased Pulse Summation Sonar) that, like TWIPS, was effective at enhancing the detectability of fish in bubble clutter, and distinguishing them from clutter (Leighton et al, 2012b). Given that modern amplifiers and emitters tend to more easily produce high fidelity copies of pulses that have differing amplitudes, as opposed to opposing phases, BiaPSS sources were more practical to produce than TWIPS sources.…”
Section: Do Whales Call In Spirals?mentioning
confidence: 99%
See 3 more Smart Citations
“…We developed a practical sonar system using this BiaPSS (Biased Pulse Summation Sonar) that, like TWIPS, was effective at enhancing the detectability of fish in bubble clutter, and distinguishing them from clutter (Leighton et al, 2012b). Given that modern amplifiers and emitters tend to more easily produce high fidelity copies of pulses that have differing amplitudes, as opposed to opposing phases, BiaPSS sources were more practical to produce than TWIPS sources.…”
Section: Do Whales Call In Spirals?mentioning
confidence: 99%
“…We proposed that, rather than being an accident, this amplitude variation might purposefully supply pairs of pulses with another difference that could exploit the fact that bubble clutter scatters nonlinearly, whilst the fish do not (Leighton et al, 2012b). We tested a range of pulses, in test tanks and simulation Leighton et al, 2012b). Figure 5 shows a pulse pair based on clicks, where each click in the pair consists of two synchronous downchirps, each covering a distinct frequency range, and as such is a commonly accepted to typify a form of emission from the Atlantic bottlenose dolphin (Tursiops truncatus; Capus et al, 2007).…”
Section: Do Whales Call In Spirals?mentioning
confidence: 99%
See 2 more Smart Citations
“…Gaussian pulses are used in this particular study, although the principle was shown to work using BiaPSS for a range of other pulses, including a linear frequency-modulated pulse and dolphin-like clicks [6]. These could be of greater use if, for example, the resonance frequencies of components were not well known before the test, or if a particular target possessed several resonances that were to be used to identify it.…”
Section: Introductionmentioning
confidence: 99%